Roles and Responsibilities of College Management Committee (CMC) in Public Colleges of Nepal: A Critical Analysis - K.C., Chitra Bahadur (International Research Journal of Parroha, 2024)
The College Management Committee (CMC) plays a crucial role in the implementation, management, and performance of public colleges in Nepal. This study aims to identify the roles and responsibilities of the CMC in public colleges within the country. Utilizing a cross-sectional quantitative design, data were collected from 400 respondents across public colleges in the Rupandehi district of Nepal. A standardized survey questionnaire was employed for data collection, followed by statistical analysis to interpret the findings. The results underscore the importance of recognizing and addressing the diverse perceptions of both teachers and students regarding the CMC's roles in educational governance and management. A significant association was found between the perspectives of teachers/CMC members and students concerning various aspects of the CMC's functions in public colleges. Understanding these differences is essential for fostering effective collaboration and communication among stakeholders, ultimately ensuring the holistic development and improvement of educational institutions in Nepal. Future research could expand the scope by incorporating additional stakeholder perspectives, such as parents, administrative staff, or external education experts. A broader range of viewpoints would provide a more comprehensive understanding of the effectiveness of the CMC.